Konsep Potensi dan Ciri-ciri Anak Berbakat dalam Pendidikan serta Layanan Pendidikan Anak Berbakat - Habsy, Bakhrudin All; Prasetyo, Intan Anggraheni Zahrin; Nabila, Fitri Ayu (TSAQOFAH, 2024)
This research aims to determine interests and talents as well as characteristics, types, characteristics, factors that influence talent potential, problems of gifted children, how to develop talents, as well as special education to help children discover their potential talents. This research method uses literature study. Through the results of the literature study, it can be concluded that there are several factors that are very important in developing talent potential, namely by knowing the child's potential first, paying attention to his intelligence quotient, providing appropriate facilities by providing illustrations to the child, showing interest to the teacher in a particular field, giving appreciation and invites you to take part in competitions.